Working with hostile and resistant teens - Campbell, Steven; Kinney, Tom; Schultz, Jeff; Attainment Co. (Boston : Attainment Co., 1993)
Counselor and social worker Steven Campbell demonstrates way to avoid the'game' structure when working with hostile and resistant teens. Case studies with David, Amanda, Sam, and Ivan are presented
Working with hostile teens (v.1) ; working with resistant teens (v.2)
Producer, Tom Kinney ; Director, Jeff Schultz ; Executive producer, Don Bastian
VHS
Keywords: Problem youth -- Counseling of; Teenagers -- Counseling of; Anger in adolescence